Estudio de factibilidad para la creación de una agencia de publicidad en la ciudad de Quevedo periodo 2013 - Morán Arriaga, Eloisa Katherine (2013)
Currently , small and large companies seeking to communicate information about their services and products to their customers, steadily, while changes are monitored in the tastes and preferences of consumers , either to increase their levels of demand , to improve the quality in their products or services, or simply to increase their profitability. Objectives that were raised in the research project were:  Develop a market study and that Financial Officer to determine the feasibility of an advertising agency in the canton Quevedo.  Conduct a technical study to determine the size, location, and technical processes for the provision of services in the advertising agency.  Analyze the market behavior through a survey of business representatives, media and graphic designers in the city of Quevedo. Among the most important services offered to this market, include Billboards, Magazines, Print Media, Market Research, TV Spot Printed, and Wedges. The project requires an initial investment of $ 34,012.98 the same, which may be funded directly, with the capital contribution by partners, or with funding from a public or private bank. In calculating, the Net Present Value (NPV) projected to five years resulting in $ 17.859,02 being demonstrated that the project is profitable and is therefore feasible Flow was taken into account. The Internal Rate of Return (IRR) was determined in 21 %, higher than the discount rate of 5 % percentage demonstrating that the project is profitable.